2003
DOI: 10.1063/1.1527914
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Kolmogorov’s model of breakup and its application into Lagrangian computation of liquid sprays under air-blast atomization

Abstract: This paper considers the breakup of liquid drops at the large Weber number within the framework of Kolmogorov’s scenario of breakup. The population balances equation for droplet radius distribution is written to be an invariant under the group of scaling transformations. It is shown that due to this symmetry, the long-time limit solution of this equation is a power function. When the standard deviation of droplet radius strongly increases and, consequently, the characteristic length scale disappears, the power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Recent studies [7,[9][10][11] have shown that old paradigms for understanding disintegration of Newtonian liquids, based on either cascade theory [12] (leading to log-normal size distributions) or maximum entropy theories [13] (leading to Poisson size distributions) do not adequately capture all physical aspects of these processes. Villermaux et al [10] show that the atomization process for Newtonian liquids can be precisely described by a fragmentationcoalescence scenario [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [7,[9][10][11] have shown that old paradigms for understanding disintegration of Newtonian liquids, based on either cascade theory [12] (leading to log-normal size distributions) or maximum entropy theories [13] (leading to Poisson size distributions) do not adequately capture all physical aspects of these processes. Villermaux et al [10] show that the atomization process for Newtonian liquids can be precisely described by a fragmentationcoalescence scenario [14].…”
mentioning
confidence: 99%
“…However, none of these studies address the role of viscoelasticity on the distribution of droplet sizes. The few attempts in the literature to address the size distributions for polymeric liquids [28,29] base their assumptions on older paradigms [12,13].…”
mentioning
confidence: 99%
“…The only macroscopic constraint on the choice of n ij arises from the conservation of mass during a single breakage event (14) and is identically satisfied by equation (13). In addition, equation (13) allows the possibility of producing distribution coefficients consistent with Kolmogorov's hypothesis (see, for instance, Gorokhovski and Saveiliev [26] or Apte et al [11]) that breakups of all sized particles produce the same number of particles.…”
Section: Resultsmentioning
confidence: 78%
“…A new approach is developed by Gorokhovski and Saveliev (2003) and Apte et al (2003) based on the Kolmogorov's scenario of the breakup of particles. Kolmogorov wrote a stochastic theory for the breakup of solid particles that describes the cascade of uncorrelated breakage events.…”
Section: Introductionmentioning
confidence: 99%